2014
DOI: 10.1007/s10534-014-9807-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of NOS-mediated ROS accumulation in an early phase Cu-induced acute cytotoxicity in MCF-7 cells

Abstract: Copper (Cu) ion is essential for the biological systems, however, high level of CuCl2 exposure causes detrimental effects, which leads to cell apoptosis. Nitric oxide (NO) is an efficient cell signal messenger, which plays an important role in cell apoptosis. However, the potential mechanism of an early phase Cu-induced acute cytotoxicity through the nitric oxide synthase (NOS) signaling pathway and its interaction has not been studied. In this report, we provide data showing that high level of CuCl2 could rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The pretreatment of MCF-7/ADR cells was consistent with that of ATP determination. Ca 2+ imaging was performed by loading cells with 2 μM Fluo-3/AM (Beyotime, Shanghai, China) as described previously . The fluorescence at different durations after irradiation was detected using a SpectraMax M2 microplate reader or visualized by CLSM (Ex/Em = 488/525 ± 20 nm).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The pretreatment of MCF-7/ADR cells was consistent with that of ATP determination. Ca 2+ imaging was performed by loading cells with 2 μM Fluo-3/AM (Beyotime, Shanghai, China) as described previously . The fluorescence at different durations after irradiation was detected using a SpectraMax M2 microplate reader or visualized by CLSM (Ex/Em = 488/525 ± 20 nm).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…A previous study demonstrates that cytosolic Ca 2+ levels increase in MCF7 cells following treatment with CuCl 2 ( 42 ). Therefore, we investigated whether CuCl 2 treatment induces a surge in cytosolic Ca 2+ and dysregulates autophagy in MN9D cells.…”
Section: Resultsmentioning
confidence: 94%
“…It has been demonstrated that apoptosis rates are correlated with Cu excess in different cell types such as liver cells (Oe et al 2016), mouse fibroblasts (Cao et al 2012), osteoblasts (Cortizo et al 2004), PC-3 human prostate cancer cells (Wang et al 2014), and P19 neurons (Jazvinšćak Jembrek et al 2014). This effect was observed in both in vivo and in vitro systems (Handy 2003;Lu et al 2006;Yu et al 2008;Wang et al 2014;Zhong et al 2015;Pramanik et al 2016). However, molecular and cellular mechanisms that link Cu to programmed cell death remain largely unknown (Jazvinšćak Jembrek et al 2014).…”
Section: Discussionmentioning
confidence: 99%